Clinical outcomes of nonsurgical root canal treatment using C-root SP combined with different obturation techniques in older patients: a randomized controlled clinical trial - Liping Dong; Jianshe Li; Peng Xue; Suixin Hu; Chen Xu; Lin Wang; Liu Liu; Qiang Luo; Huixia He; Fei Chen (BMC Oral Health)
Abstract Background To evaluate the clinical efficacy and outcomes of C-Root SP bioceramic-based sealers combined with different obturation techniques in nonsurgical root canal treatment for older patients. Methods This prospective, single-center, single-blind, parallel, randomized clinical trial included 240 patients aged ≥ 60 years. Patients were randomly divided into four treatment groups. Group A: C-Root SP combined with single-cone (SC); Group B: C-Root SP combined with warm vertical compaction (WVC); Group C: C-Root SP combined with cold lateral condensation (CLC); Group D: iRoot SP combined with SC (Control). All teeth were subjected to root canal filling using the corresponding methods 7–10 days after root canal preparation and medication. The duration of obturation was recorded. Periapical radiographs were obtained immediately after obturation to determine the length of root canal filling, and postoperative pain on days 1, 2, and 7 was documented. The treatment outcomes based on clinical signs and symptoms as well as periapical index (PAI) were analyzed at 1 year postoperatively. Results Groups A and D exhibited significantly higher filling efficiency than groups B and C (P < 0.001). No significant differences were observed in the length of obturation between the groups (P > 0.05). Postoperative pain decreased over time in all groups, with group A showing significantly lower pain rates on day 1 than the other groups (P < 0.05). After 1 year, all groups exhibited considerable reductions in the PAI scores, with success rates ranging from 91.23 to 94.83%; however, no significant differences were observed between them (P > 0.05). Conclusions C-Root SP combined with different obturation techniques yielded similar outcomes to iRoot SP combined with the SC technique in terms of filling length, success rate, and changes in PAI scores. The SC technique demonstrated significant advantages in terms of clinical efficiency and may reduce early postoperative pain when combined with C-Root SP. Trial registration The study was retrospectively registered in chictr.org.cn with the identifier: ChiCTR2400092580 on 11/19/2024.